A prospective multicenter study on mucormycosis in India: Epidemiology, diagnosis, and treatment. (1st August 2018) - Prakash, Hariprasath; Ghosh, Anup Kumar; Rudramurthy, Shivaprakash Mandya; Singh, Pankaj; Xess, Immaculata; Savio, Jayanthi; Pamidimukkala, Umabala; Jillwin, Joseph; Varma, Subhash; Das, Ashim; Panda, Naresh K; Singh, Surjit; et al.
Abstract: Mucormycosis due to Mucorales is reported at large numbers in uncontrolled diabetics across India, but systematic multicenter epidemiological study has not been published yet. The present prospective study was conducted at four major tertiary care centers of India (two in north and two in south India) during 2013–2015 to compare the epidemiology, treatment strategies and outcome of mucormycosis between the two regions. Molecular techniques were employed to confirm the identity of the isolates or to identify the agent in biopsy samples. A total of 388 proven/probable mucormycosis cases were reported during the study period with overall mortality at 46.7%. Uncontrolled diabetes ( n = 172, 56.8%) and trauma ( n = 31, 10.2%) were the common risk factors. Overall, Rhizopus arrhizus ( n = 124, 51.9%) was the predominant agent identified, followed by Rhizopus microsporus ( n = 30, 12.6%), Apophysomyces variabilis ( n = 22, 9.2%) and Rhizopus homothallicus ( n = 6, 2.5%). On multivariate analysis, the mortality was significantly associated with gastrointestinal (OR: 18.70, P = .005) and pulmonary infections (OR: 3.03, P = .015). While comparing the two regions, majority (82.7%) cases were recorded from north India; uncontrolled diabetes ( n = 157, P = .0001) and post-tubercular mucormycosis ( n = 21, P = .006) were significantly associated with north Indian cases. No significant difference was noted among the species of Mucorales identified and treatment strategies between the two regions. The mortality rate was significantly higher in north Indian patients (50.5%) compared to 32.1% in south India ( P = .016). The study highlights higher number of mucormycosis cases in uncontrolled diabetics of north India and emergence of R. microsporus and R. homothallicus across India causing the disease.